APPLICATION OF GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS ON NEWTON'S LAW MATERIAL IN SENIOR HIGH SCHOOL - Sadam Husen; Zohratul Amni (Jurnal Inovasi Fisika dan Edukasi, 2025)
Critical thinking skills are essential competencies in 21st century physics learning, but in practice, students often have difficulty in understanding the concept of Newton's Law in depth due to teacher-centered learning methods. This study aims to analyze the effectiveness of the guided inquiry learning model in improving students' critical thinking skills on Newton's Law material at the Senior High School level. The type of research used is quantitative with a quasi-experimental approach using a nonequivalent control group design. The research subjects consisted of two classes, namely the experimental class taught using the guided inquiry model and the control class taught with a conventional approach. Data were collected through critical thinking skills tests in the form of open-ended descriptions given before and after treatment (pretest and posttest). The instrument was validated by experts and tested for reliability using Cronbach's Alpha. Data were analyzed descriptively and inferentially using t-test of two independent samples after going through normality and homogeneity tests. The results showed that there was a significant difference between the posttest scores of the experimental group and the control group (p < 0.05), with the average score of the experimental group higher. This shows that the guided inquiry learning model is effective in improving students' critical thinking skills. Conclusion.